2017
DOI: 10.1080/1828051x.2017.1360160
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric and sorghum for egg-laying quails

Abstract: The aim of the present study was to assess the effect of adding different turmeric amounts to sorghum-based diets for Japanese quails on animal performance, animal metabolism, yolk colour, egg quality, blood and liver biochemical parameters and sensory attributes of the eggs. The study included 210 egg-laying quails aged 50 days and lasted for 90 days. The study had a completely randomised design with six treatments and five replicates with seven birds per replicate. A control corn-based feed and sorghum-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
4
11
2
Order By: Relevance
“…Independently to the dietary treatment, the weight of the eggs produced by quails in the present experiment was higher (14.5 g) than values commonly found in literature [18]. Birds of the present study were almost at the end of their productive career, whereas most research studies considered 8–12 weeks-old birds [33].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Independently to the dietary treatment, the weight of the eggs produced by quails in the present experiment was higher (14.5 g) than values commonly found in literature [18]. Birds of the present study were almost at the end of their productive career, whereas most research studies considered 8–12 weeks-old birds [33].…”
Section: Discussioncontrasting
confidence: 49%
“…The pH values recorded during the storage trial on quails’ eggs were slightly lower than values presented by Silva et al [18]. This finding was not surprising as albumen pH gives a clear indication of the freshness of the egg and, in the present experiment, pH measurement was conducted the day after the eggs were laid.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…[1] observed a greater presence of white color in the egg yolks when they replaced 50% of the corn from the layer diet by sorghum and used 2% of dry turmeric rhizome. Also [14] concluded that dry turmeric rhizome was not a good pigment for quail egg yolk staining.…”
Section: Egg Qualitymentioning
confidence: 99%
“…Eggs are low-cost source of high-quality protein, lipids, vitamins and minerals (Miranda et al 2015) with rapidly increasing production, expected to reach the 89 million ton by 2030 (Secci et al 2018). In this respect, quail egg production has been increasing in recent years due to early sexual maturity, short generation interval, high laying rate and limited feed and space requirements per bird (Gonz alez 1995;Silva et al 2018). On the other hand, the higher need to poultry production increases the need to further feed, accounting for more than 65% of variable expenses of producing poultry products (Kiarie et al 2013).…”
Section: Introductionmentioning
confidence: 99%